Technology-assisted doctoral supervision: Practice and lessons from Anglo-Saxon universities in Cameroon - Etomes, S.; Aluko, F. R. (South African Journal of Higher Education, 2025)
This study investigates how technology-assisted doctoral supervision in teacher education can improve the quality of the supervision process in Cameroon. It is an exploratory sequential mixed method which involves an initial qualitative phase with PhD students followed by a quantitative phase with PhD supervisors. The study was situated in the Affordances Theory mooted by Gibson (1979) that explains how technological affordances can support the supervisory process. The snowball sampling technique was used to select n=80 PhD students using 9 focus group discussion and n=210 doctoral supervisors who responded to the questionnaire. The qualitative data was analysed using thematic-content method while the quantitative data was analysed using the statistical package for social sciences (SPSS) version 25.0, frequency counts and percentages and Pearson parametric test. Findings showed that there is a significant and positive relationship between the use of ICT tools on doctoral supervision and students’ output. Also, the non-use of ICT tools was found to have a slightly negative effect on doctoral supervision. While the use of ICTs by both supervisors and PhD supervisees was evident, it was mostly limited to phone calls and WhatsApp due to inadequate skills in ICT. With issues of globalization, crisis and pandemics, technology is relevant to improve on doctoral supervision. It is, therefore, recommended that the use of technology should be included in postgraduate pedagogy and teacher education to improve on the quality of doctoral supervision. A similar research work can be carried out in other universities in Cameroon and developing economies to corroborate the findings. A comparative analysis is relevant for generalization and improvement in doctoral supervision.